Group discussion in a small setting as part of the team-based learning strategy: a potential method for distance learning in pharmacology - Kucher, T. V.; Кучер, Тетяна Володимирівна (Запорізький державний медико-фармацевтичний університет, 2025)
Effective pharmacology teaching is necessary to ensure that medical students were especially competent in the use of drugs. A safe and effective prescription - is a fundamental skill that must be purchased by graduates of medical schools, as improper drugs prescription may cause exacerbation and prolongation of illness or damage to the patient.
Keywords: Pharmacology; student clinical thinking; team based learning; problem-based learning; analytical skills